PELABELAN ORANG MINANGKABAU PADA PELAKU PENYIMPANGAN SOSIAL: STUDI KASUS PADA DUA NAGARI DI SUMATERA BARAT - Erianjoni, Erianjoni (Humanus, 2015)
This article discusses the labeling in Minangkabau society, in a society labeling is considered to be part of a local term that can be understood by the local community. The labelling of the society’s behavior is assumed to be different in each village in West Sumatra because of the Minangkabau people have different customs in each region in West Sumatra including the ‘darek’ (plateau) and pasisie (coastal) regions, because the Minangkabau is known for its unique custom ‘adat Salingka nagari'. Minangkabau cultural distinctiveness on the labeling of perpetrators of deviance is very interesting to be elaborated deeper, thus the researcher wrote this article.Keywords: label, committer, social deviation